Maximizing English Speech on YouTube Videos to Enrich Students’ Vocabulary - Ihdal Bayu Pamungkas; Raida Asfihana; Afifah Linda Sari (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
Learning vocabulary is essential in language learning since it will help students to master a language as well as communicate with others effectively using various words. This classroom action research, which followed Kemmis and McTaggart’s model, aimed to investigate the effectiveness of utilizing English Speech on YouTube Videos to enrich students’ English vocabulary. The participants of this study were the seventh graders of the Language Class in SMP Muhammadiyah Banjarbaru. The results revealed that maximizing English Speech on YouTube Videos can effectively boost students’ vocabulary building since the scores of the pre-test, post-test 1, and post-test 2 showed different and significant improvements. Moreover, the classroom environments and the students’ enthusiasm improved as well. The classroom became conducive and interactive, and the students were excited and enthusiastic and genuinely paid attention to the videos and the teacher’s explanations.